2010
DOI: 10.1007/s10511-010-9098-9
|View full text |Cite
|
Sign up to set email alerts
|

Redshifts of 19 Shakhbazian compact groups of galaxies

Abstract: Redshifts of another ten memberswere taken from the NED. We found that nine out of 118 candidate member galaxies are stars, and twelve galaxies are not members of the corresponding groups and are projected over them. The group ShCG 168 is the core of a cluster. The groups ShCG 276, ShCG 298, and ShCG 303 are either strongly contaminated by field galaxies with redshift differing not very much from that of the corresponding group, or are the results of a chance projection of field galaxies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23]. A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23].…”
Section: Observations and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23]. A large number of interacting galaxies are detected among ShCG members [14,[15][16][17][18][19][20][21][22][23].…”
Section: Observations and Resultsmentioning
confidence: 96%
“…Spectral and photographic observations of a large number of ShCG groups have been made by Tiersch et al [14 and references therein] and Tovmassian et al [15][16][17][18][19][20][21][22][23]. It was shown that the majority of the candidate group members were galaxies with accordant radial velocities (usually < 1000 km s -1 ).…”
mentioning
confidence: 99%